Evaluación técnico financiera del diseño de cinco pilotos de inyección de agua para el campo ermitaño de la cuenca del Valle Medio Del Magdalena (2018)
The present project is carried out with the aim of designing five pilots of waterflood using the Montecarlo Simulation for the Ermitaño Field of the Middle Magdalena Valley Basin, which is operated by Ecopetrol S.A. It begins by explaining the current conditions of the field, Its geography location and its geological characteristics are described. Then the reservoirs are characterized, focused on how the properties of rock and fluid have been affected by the vertical relief and the compartmentalization. A description of the software used is made and a prediction model previously created by the company is selected, which is used to evaluate with probability distributions the operational factors that affect the behavior of the water injection process in the field, allowing to determine the variables to sensitize to carry out the design of the pilots.